If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(n) = 195 + -15n Multiply f * n fn = 195 + -15n Solving fn = 195 + -15n Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'n'. f = 195n-1 + -15 Simplifying f = 195n-1 + -15 Reorder the terms: f = -15 + 195n-1
| 8x-14x=-20-(-2) | | 2m^-5n7/14m^6n3 | | -54=-9n | | 5(3+x)=(x-3)-4x | | x-40=.9x | | 3.7x+1.2=2.31 | | 5.2x+1.4=1.868 | | 2x-3=1x+5 | | 2(10x-3)=54 | | 4a-3(4-2a)= | | -0.4x=60 | | 1/42x-7/25 | | ln(x)=8.27 | | -3x+11=56 | | 23-4x-8+9x=-30 | | -2f+4(-2f+5)-3=17 | | 6x+12=20x-24 | | 10(4k+6t+3)= | | -1.5n-12=94 | | 4.4x-0.2=26.2 | | 0=7/2x-21/2 | | m/3=-27 | | 8x-31/6=x-5 | | y/18=64 | | (3x^2-4x)(2x^3+3x-1)=y | | 3(x-7)=(3x+2)(2x+1) | | 2u-u= | | p/3asfdr | | w/7.5=52 | | 5n=10-5n | | 3x(2x+7)= | | 9.8/1.4 |